PENGARUH PROFITABILITAS, CAPITAL INTENSITY, LEVERAGE, INVENTORY INTENSITY, DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2023) - Susanto, Florencia Angeline; Jusuf, A An Arief (Bajang Institute, 2025)
Taxes are the largest source of state revenue, used to finance development and government operations for the welfare of the public. However, for companies, taxes are often considered a burden because they reduce profits generated from business activities. This situation has led to the emergence of tax avoidance, a practice carried out legally. This study aims to analyze the effect of profitability, capital intensity, leverage, inventory intensity, and transfer pricing on tax avoidance in Consumer non-cyclical sector companies listed on the Indonesia Stock Exchange for the period of 2019–2023. The research uses secondary data from the annual financial reports of 131 companies. Using a purposive sampling technique, 21 companies were obtained as the sample. Data were analyzed using the Gretl for Windows software. The results show that leverage and transfer pricing have a significant negative effect on tax avoidance, while profitability, capital intensity, and inventory intensity have no significant effect. These findings indicate that companies with high levels of leverage and transfer pricing tend to reduce their tax avoidance practices. In conclusion, leverage and transfer pricing are important determinants of tax avoidance behavior, while the other variables have no significant influence.